Transumbilical endoscopic cholecystectomy in a porcine model - Zhu,Hong-Yi (2013)
PURPOSE: Natural orifice transluminal endoscopic surgery (NOTES) is a new technique. This study describes our initial experience of NOTES and investigates the feasibility of transumbilical endoscopic cholecystectomy (TUEC). METHODS: Eight domestic pigs were submitted to TUEC. After establishment of pneumoperitoneum, a bi-channel endoscope was placed through an infra-umbilical trocar. The gallbladder fundus was lifted by a grasper. The cystic duct and artery was dissected with a flexible hook and clipped by a clip fixing device. The specimen was extracted through the infra-umbilical trocar. RESULTS: The mean operation time was 114 minutes, ranging from 75 to 155 minutes. All the gallbladders were removed successfully. There was one case of subtotal resection, two cases of bleeding and three cases of bile leakage. CONCLUSION: Transumbilical endoscopic cholecystectomy is feasible although it needs more support of experiments and techniques before being applied on human subjects.